Post-partum evaluation of women's satisfaction from the cooperation with the gynecologists and midwives in Cyprus: A pilot study - Stylianides, Costas; Raftopoulos, Vasilios (My University, 2014)
Objective Assessment of the cooperation between women who have given birth and their midwives and gynecologists during pregnancy and delivery. Method The study participants were 167 women who had recently given birth in the public perinatal health facilities in Cyprus. They completed an anonymous questionnaire that was based on bibliographical evidence and included a Greek version of the Kuopio Instrument for Mothers (KIM) scale. Results The majority of the participants were public or private employees, married and graduates of tertiary level education. They reported that the gynecologists had adequately respected the women's body during the examinations and procedures, explained the reasons for the procedures and informed them about the progress of the delivery. The elements that were not extensively discussed included: (a) The need for using certain instruments during the delivery, and (b) the feeling that women could not take part in the decisions taken during the delivery. The midwives were reported to have adequately respected the women's bodies during the examinations and procedures, informed them about the alternative methods of pain relief (e.g. mobilisation, breathing techniques) and enabled them to express freely their feelings about the delivery. What was not adequately discussed included: (a) Planning the delivery with the midwife, and (b) explanation of the need for using certain instruments. No significant difference was demonstrated in their co-operation with the gynecologist between women who had a vaginal delivery or cesarian section (CS), between younger and older women or between those that would choose to have a vaginal delivery or CS if given the option. The women who had a vaginal delivery reported statistically significant better cooperation with the midwives than those who had a CS (p=0.021). Conclusions The women who use the public perinatal healthcare services in Cyprus reported satisfaction with their cooperation with the midwives and gynecologists, during both their pregnancy and their delivery, with the midwives evoking a higher level of satisfaction. The mode of delivery appeared to be the determinant factor in this cooperation, with the women who had a vaginal delivery reported higher satisfaction rates in the cooperation they had with the midwives than with the gynecologists.
Keywords: Perinatal care; Pregnancy; Quality of care; Satisfaction